2012
DOI: 10.1111/j.1552-3934.2012.02120.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Socialization and Information Source on Financial Management Behaviors among Low‐ and Moderate‐Income Adults

Abstract: Previous studies on financial socialization have focused on adolescents or college students. This study examined the effect of financial socialization on the financial behaviors of adults aged 24–66 from low‐ and moderate‐income households. Data from the NC‐1172 Complex Nature of Saving data set were analyzed using ordinary least squares regressions and logistic regressions. The four dependent variables were spending less than income, making financial plans, monitoring spending, and having savings goals. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 27 publications
(50 reference statements)
1
20
2
4
Order By: Relevance
“…communication is positively related to children's money management as adults (e.g., Cho, Gutter, Kim, & Mauldin, 2012) and children's actual financial behaviors (e.g., Clarke et al, 2005;Shim, Barber, Card, Xiao, & Serido, 2010;Webley & Nyhus, 2006). Further, discussing financial matters with children can reduce children's economic stress (Serido, Shim, Mishra, & Tang, 2010).…”
mentioning
confidence: 97%
“…communication is positively related to children's money management as adults (e.g., Cho, Gutter, Kim, & Mauldin, 2012) and children's actual financial behaviors (e.g., Clarke et al, 2005;Shim, Barber, Card, Xiao, & Serido, 2010;Webley & Nyhus, 2006). Further, discussing financial matters with children can reduce children's economic stress (Serido, Shim, Mishra, & Tang, 2010).…”
mentioning
confidence: 97%
“…Cho, Gutter, Kim and Mauldin (2012) support this, concluding that those who earn higher incomes monitored their spending less frequently. It is interesting that those earning lower salaries also place more importance on giving their children monetary freedom than do those with higher incomes.…”
Section: Discussionmentioning
confidence: 91%
“…Most of the respondents who have their parents in monitoring their expense in the childhood age have less worry about their finance and has no full responsibility to manage their financial management. Meanwhile, Cho et al (2012) stated that primary agents do not influence financial management behavior. Thus, the hypothesis is as follows, H5: There is an influence between primary agents towards financial management behavior to the millennial generation in Surabaya.…”
Section: Financial Socialization Agentmentioning
confidence: 99%
“…The more they gain the learning and information process from the secondary agents, their financial management behavior will be better. Cho et al (2012) declared that there is a positive influence between secondary agents towards financial management behavior. It is in contrast with the study conducted by Falahati & Paim (2011), where they found that secondary agents have a negative influence on financial management behavior.…”
Section: Financial Socialization Agentmentioning
confidence: 99%
See 1 more Smart Citation